2023
DOI: 10.29173/cjfy29896
|View full text |Cite
|
Sign up to set email alerts
|

Students' Attitude towards Political Participation and Democratic Values in Nigeria: Critical Democracy Education Implications

Abstract: This study investigated the attitudes of university students toward political participation, as well as four other selected democratic values – freedom and liberty, human rights/human rights protest, corruption resistance, and separation of powers in Nigeria. A descriptive survey design, with a tool entitled ‘Attitude towards Democratic Values Questionnaire (ADVQ)’, was used to collect data from randomly selected 250 undergraduate students (male = 120; female = 130) from a university in Nigeria. Six research q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
0
0
Order By: Relevance
“…These findings align with a study on the attitude of university students towards selected democratic values in Nigeria, which indicated positive attitudes towards all selected democratic values among university students (Obiagu, Machie & Ndubuisi, 2023). However, a study on political socialisation as a correlates of youths' political attitude in Ekiti State, Nigeria, opposed the findings of this study, which reported that youths' political attitude differs based on their educational status with education predicting youths' political attitude to a large extent, as youths are not encouraged to participate in democratic processes except when they are financially induced (Adekanmbi, Ajibefun & Ojomo, 2020).…”
Section: Discussion Of Findingssupporting
confidence: 89%
“…These findings align with a study on the attitude of university students towards selected democratic values in Nigeria, which indicated positive attitudes towards all selected democratic values among university students (Obiagu, Machie & Ndubuisi, 2023). However, a study on political socialisation as a correlates of youths' political attitude in Ekiti State, Nigeria, opposed the findings of this study, which reported that youths' political attitude differs based on their educational status with education predicting youths' political attitude to a large extent, as youths are not encouraged to participate in democratic processes except when they are financially induced (Adekanmbi, Ajibefun & Ojomo, 2020).…”
Section: Discussion Of Findingssupporting
confidence: 89%